Santri Management in Pesantren (Islamic Boarding Schools) - Rini Setyaningsih; Anan Surya; Arrum Intan Sari (At-Ta'lim : Media Informasi Pendidikan Islam, 2025)
ENGLISH: Santri Management in Pesantren (Islamic Boarding Schools)Objective: This study aims to analyze the management of students at the Dar El-Hikmah Islamic Boarding School in Pekanbaru through a review of the guidance, supervision, strengthening of student organizations, and implementation of extracurricular activities in the daily lives of students. Method: This study uses a qualitative approach with a case study design. Data was collected through intensive observation for one month, in-depth interviews, and data analysis using the Miles and Huberman model. Results: Student management at the Dar El-Hikmah Islamic Boarding School is carried out in a structured manner through the supervision of daily activities, continuous moral guidance, strengthening the student organization as a forum for leadership, and organizing extracurricular activities based on interests and talents, a whole range of responsibilities, and the social competence of students. Conclusion: The digital literacy capacity of students and the use of technology in the management system are still limited, so Islamic boarding schools need to strengthen these areas to adapt to the demands of the modern era. Contribution: This study reveals a structured santri development ecosystem, encompassing character development, supervision, organization, and extracurricular activities, which forms an integrative management system and opens up opportunities for pesantren transformation to ensure relevance and resilience in the modern era: Keywords: Student Management; Islamic Boarding School; Character DevelopmentINDONESIAN: Manajemen Santri di Pondok Pesantren Tujuan: Penelitian ini bertujuan menganalisis manajemen santri di Pondok Pesantren Dar El-Hikmah Pekanbaru melalui kajian terhadap proses pembinaan, pengawasan, penguatan organisasi santri, serta pelaksanaan kegiatan esktrakurikuler yang diterapkan dalam kehidupan sehari-hari santri. Metode: Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus. Data dikumpulkan melalui observasi intensif selama satu bulan, wawancara mendalam, analisis data menggunakan model Miles dan Huberman. Hasil: Manajemen santri di Pondok Pesantren Dar El-Hikmah dialksanakan secara terstruktur melalui pengawasan kegiatan harian, pembinaan akhlak secara berkelanjutan, penguatan organsiasi santri sebagai wadah kepemimpinan, serta penyelenggaraan kegiatan ekstrakurikuler berbasis minat dna bakat, seluruh rangkaian tanggung jawab, serta kompetensi sosial santri. Kesimpulan: Kapasitas literasi digital santri dan pemanfaatan teknologi dalam system manajemen masih terbatas, sehingga pesantren perlu melakukan penguatan di bidang tersebut untuk menyesuaikan diri dengan tuntutan era modern. Kontribusi: Penelitian ini mengungkap ekosistem pembinaan santri yang terstruktur, mencakup akhlak, pengawasan, organisasi, dan ekstrakurikuler, yang membentuk manajemen integratif dan membuka peluang transformasi pesantren untuk relevansi dan ketahanan di era modern.